Model Pembelajaran Saintaq Pendidikan Agama Islam Sebagai Bentuk Integrasi Sains dan Agama dalam Menghadapi Tantangan Abad Ke 21 (Integrasi Metodologi/ Proses Pembelajaran Aqidah) - Surahman Surahman (STAIN Bengkalis, 2020)
Al-Qur'an through its verses invites people to think about various kinds of signs of Allah's power in various ways, including a scientific approach. This is in line with the demands of high school learning which are contained in the 2013 curriculum. However, it needs to be realized that this creates a problematic process, especially for Islamic Religious Education teachers when teaching Aqedah material. This problem can be seen from the readiness of the teacher to use lesson plans, methods, student assignments, and material and module design. Based on this indicator, the conclusion is drawn that Islamic Religious Education teachers are still less able to teach Aqedah material scientifically/ scientifically at Senior High Schools. Responding to this problem, the researchers on the library research method to create a scientific/ scientific model of Aqedah material combination in Islamic Religious Education learning which is packaged in the title